Morphological and Molecular Descriptions of Macracanthorhynchus ingens (Acanthocephala: Oligacanthorhynchidae) Collected from Hedgehogs in Iran - Najjari, Mohsen; Tavakoli Kareshk, Amir; Darvishi, Mohammad; Barzegar, Gholamreza; Dusti, Majid; Namaei, Mohammad Hasan; Shafaie, Ebrahim; Solgi, Rahmat (Interdisciplinary Perspectives on Infectious Diseases, 2022)
Aim. Limited data exist on acanthocephalan infections of hedgehogs in the world. Our objective was to investigate the prevalence and distribution of Macracanthorhynchus ingens infection in hedgehogs between August 2021 and March 2022 (n = 30) in the east of Iran. Methods. At first, infection with M. ingens was diagnosed based on morphologic features of the adults such as body length, proboscis, and hooks. Spindle-shaped eggs (mean length, 99.1 microns; mean width, 60.1 microns) were obtained from the body cavity of gravid female specimens. Results. The molecular analysis based on 18S rDNA and COX 1 genes confirmed the morphological identification of isolated M. ingens. The prevalence of M. ingens in our sample was 13.3% with 1–10 worms per infected host. Conclusion. In this study, we identify M. ingens as zoonotic species in hedgehog carcasses for the first time that passed eggs and adult worms, indicating parasite maturation and reproduction. There are a few studies on acanthocephalans in Iran. Therefore, more comparative studies are needed to determine the status of these species.